Maternal supplementation of Lonicera flos and Scutellaria Baicalensis mixed extracts improve reproduction performance and metabolic health through modulating gut microbiota during pregnancy - Mu Wang; Shengnan Yin; Jinghua Cheng; Yuqiang Guo; Huiyuan Lv; Siwen Jiang; Jian Peng; Yuanfei Zhou (BMC Veterinary Research)
Abstract Background This study aimed to evaluate the impacts of dietary supplementation with a combination of plant extracts on performance, metabolic health, and gut microbiota of sows. A total of 1003 crossbred pregnancy sows (DanBred Landrace × DanBred Yorkshire, mean parity 4.44 ± 1.84) were assigned to one of the two dietary treatments: a control group (CON, basal diet) and a Lonicera flos and Scutellaria baicalensis mixed extracts group (LSE, basal diet supplemented with 0.5 g/kg of mixed extracts). Results Supplementation of LSE increased (P < 0.05) the numbers of total born, litter weight and average piglet weight on L21 d, average daily feed intake, and survival rate of piglets during lactation. Compared to CON, LSE group reduced (P < 0.05) interleukin-6 (IL-6) concentration in the feces and plasma on G109 d, while increased (P < 0.05) interleukin-10 (IL-10) concentration on G109 d and on L3 d. Supplementation of LSE had lower (P < 0.05) plasma reactive oxygen species levels on G30 d and on L3 d, and had a reducing tendency (P = 0.07) for thiobarbituric acid reactive substances concentrations and a trend toward increased (P = 0.08) value of homeostatic model assessment of insulin sensitivity of sow plasma on G109 d. In addition, supplementation of LSE increased (P < 0.05) the abundance of Firmicutes and Proteobacteria and decreased (P < 0.05) the abundance of Bacteroidetes and Spirochaetes on G109 d. The abundance of Christensenellaceae_R_7_group, UCG_002, Clostridium_sensu_stricto_1, Escherichia_Shigella, un_f__Christensenellaceae, Bacteroides, and Terrisporobacter were significantly increased (P < 0.05) in the LSE diet group. The abundance of Christensenellaceae_R_7_group, UCG_002 and un_f__Ruminococcaceae were positively correlated with plasma IL-10 (P < 0.01), and negatively correlated with plasma IL-6 and TBARS levels. Conclusions This study demonstrates that dietary supplementation with Lonicera flos and Scutellaria baicalensis mixed extracts (LSE) at 0.5 g/kg during gestation significantly improves reproductive performance and metabolic health in sows, likely through modulating gut microbiota composition.The observed improvements in performance and health parameters coincide with microbiota-driven inflammation attenuation and redox balance restoration, suggesting a gut-immune axis regulatory role of LSE.